Membangun Citra, Mencuri Perhatian: Strategi Branding Politik Sherly Tjoanda di TikTok - Akbar, Shafa' Salsabila; Rahmanto, Andre Noevi; Anshori , Mahfud (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to analyze the political branding strategy of Sherly Tjoanda through her TikTok account @sherlytjoanda during the first 100 days of her term as Governor of North Maluku for the 2025–2030 period. The study applies the concept of personal political branding with seven key indicators: competence & energy, sincerity & agreeableness, excitement, openness, sophistication, ruggedness, and conscientiousness. The research method used is qualitative content analysis with a descriptive approach. Data was obtained from 194 TikTok videos, which were then categorized according to the relevant indicators. The findings reveal that the most dominant indicators are sincerity & agreeableness (161 times), conscientiousness (149 times), and competence & energy (123 times). Other indicators—sophistication (122 times), openness (63 times), excitement (48 times), and ruggedness (45 times)—serve as supporting elements. These results indicate that Sherly Tjoanda constructs a political image of integrity, relatability, and performance orientation by utilizing TikTok as a strategic medium, representing women’s political leadership in the digital era.